A high-transparency and ultra-low-viscosity sodium carboxymethyl cellulose product and its preparation method and application

By improving the process flow and selecting natural cellulose with low polymerization, the existing paper-making ultra-low viscosity carboxymethyl cellulose products have been solved, and a high-permeability ultra-low viscosity carboxymethyl cellulose sodium product with excellent performance has been prepared, meeting the high standards of customers.

CN116655810BActive Publication Date: 2025-04-04CHONGQING LIHONG FINE CHEM
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310775909.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-04-04
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

The existing paper-making ultra-low viscosity carboxymethylcellulose sodium products are insufficient in aqueous solutions, resulting in defects in certain special areas.

Method used

By using natural cellulose with low polymerization (such as wood pulp, bamboo pulp, cotton, straw fiber, etc.) and improving the process flow, including crushing, oxidizing agent treatment, acidizing, alkali treatment and post-treatment steps, a high permeability and ultra-low viscosity carboxymethylcellulose sodium product with excellent performance is prepared.

Benefits of technology

It achieves high transparency, good suspension ability and solubility of the product, and meets customers' high standards for substitution, viscosity, pH, transparency and fiber content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a high-transmittance ultra-low-viscosity sodium carboxymethyl cellulose. The present invention adopts natural cellulose (wood pulp, bamboo pulp, cotton, straw fiber, etc.) with a low degree of polymerization, improves the product quality through process improvement, and obtains a high-transmittance ultra-low-viscosity sodium carboxymethyl cellulose product with excellent characteristics. Its main quality indicators have reached the degree of substitution ≥0.6, 4% B type ≤50mPa.s, pH value 6.0-8.5, transparency ≤2.0, fiber content ≤3.0, and can meet customer requirements at the application end, especially the low-viscosity CMC required in special industrial fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of synthesis of ultra-low-viscosity sodium carboxymethyl cellulose for papermaking grade, and relates to a high-transparency ultra-low-viscosity sodium carboxymethyl cellulose product and a preparation method and application thereof. Background Art

[0002] Sodium carboxymethyl cellulose (CMC) is a high polymer fiber ether obtained by chemical modification of natural cellulose. Sodium carboxymethyl cellulose is the main ionic cellulose gum, with the appearance of white fibrous or granular powder, odorless, tasteless, and insoluble in organic solvents such as ethanol, ether, and isopropanol. Sodium carboxymethyl cellulose has the properties of emulsification, thickening, bonding, water retention, and suspension. It is currently the most widely used and largest amount of cellulose. Sodium carboxymethyl cellulose is widely used in food, medicine, petroleum, coatings, papermaking, cosmetics, lithium-ion batteries and other fields. In the food field, sodium carboxymethyl cellulose can be used as an emulsifier stabilizer and thickener, which has the effects of improving product flavor and extending product storage time; in the pharmaceutical field, sodium carboxymethyl cellulose can be used to relieve symptoms such as dry eyes, eye burning and stinging.

[0003] According to the length of the product molecular chain, sodium carboxymethyl cellulose can be divided into several categories: ultra-low viscosity sodium carboxymethyl cellulose, low viscosity sodium carboxymethyl cellulose products, medium viscosity sodium carboxymethyl cellulose products and high viscosity sodium carboxymethyl cellulose products. Ultra-low viscosity sodium carboxymethyl cellulose (hereinafter referred to as CMC) is often used in the preparation of coatings for coated paper production. It can be used as an excellent water-retaining agent, as well as an auxiliary adhesive and rheology modifier. It is characterized by low viscosity, usually 4% B type ≤50mPa), high appearance requirements, but due to the large amount of viscosity reducers added, the substitution uniformity in the CMC generation process is destroyed, the product aqueous solution has poor transparency, and the intrinsic quality is poor, resulting in defects in some special fields.

[0004] The existing paper-grade ultra-low viscosity CMC on the market, although the viscosity can meet the needs of customers, will cause problems when customers use it, such as the transparency of the aqueous solution does not meet the standard, resulting in the difficulty in controlling the precipitation amount of the solution system and observing the dispersion uniformity, poor fiber and easy to block the network, etc.

[0005] Therefore, how to prepare a paper-grade high-transparency and ultra-low-viscosity CMC product with better transparency, suspension ability and solubility as well as other high-quality indicators has become one of the urgent problems to be solved by many front-line researchers in the industry and is of great significance. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a high-transmittance ultra-low viscosity sodium carboxymethyl cellulose product and its preparation method and application. The high-transmittance ultra-low viscosity sodium carboxymethyl cellulose product prepared by the present invention has excellent performance and parameters, can meet customer requirements at the application end, and the preparation method is simple and can be scaled up to industrial production, which is more suitable for the promotion and application of industrial production.

[0007] The present invention provides a high-transparency and ultra-low-viscosity sodium carboxymethyl cellulose, wherein the degree of substitution of the sodium carboxymethyl cellulose is greater than or equal to 0.6;

[0008] The 4% viscosity of the sodium carboxymethyl cellulose is less than or equal to 50 cps;

[0009] The pH of the sodium carboxymethyl cellulose is 6.0 to 8.5;

[0010] The transparency of the sodium carboxymethyl cellulose is less than or equal to 2.0;

[0011] The fiber content of the sodium carboxymethyl cellulose is less than or equal to 3.0.

[0012] Preferably, the sodium carboxymethyl cellulose is prepared from natural cellulose;

[0013] The natural cellulose includes one or more of wood pulp, bamboo pulp, cotton and straw fiber;

[0014] The 4% viscosity is the 4% viscosity measured by a rotational viscometer at 25°C.

[0015] Preferably, the degree of polymerization of the natural cellulose is 400 to 1000;

[0016] The 4% viscosity is specifically 4% B-type viscosity;

[0017] The sodium carboxymethyl cellulose is papermaking grade sodium carboxymethyl cellulose.

[0018] The present invention provides a method for preparing high-transparency and ultra-low-viscosity sodium carboxymethyl cellulose, comprising the following steps:

[0019] 1) crushing natural cellulose and then treating it with an oxidant to obtain a raw material;

[0020] Premix chloroacetic acid and alcohol into sour wine, put part of the sour wine into a container, then add the raw material and another part of the sour wine to acidify;

[0021] 2) After the acidification is completed, the system temperature is lowered, alkali is added for alkali treatment, the temperature is raised again for reaction, and the temperature is lowered for post-treatment to obtain sodium carboxymethyl cellulose.

[0022] Preferably, the natural cellulose includes one or more of wood pulp, bamboo pulp, cotton and straw fiber;

[0023] The crushing is specifically crushing into a fluffy state;

[0024] The length of the crushed natural cellulose is less than or equal to 3 mm;

[0025] The oxidant includes one or more of an inorganic acid, an organic acid and ozone;

[0026] The oxidant treatment time is 0.5 to 1 hour.

[0027] Preferably, the inorganic acid comprises hypochlorous acid;

[0028] The organic acid includes oxalic acid;

[0029] The mass ratio of the chloroacetic acid to the alcohol is 2.6:1;

[0030] The mixing temperature was 50°C.

[0031] Preferably, the temperature of the portion of sour wine placed in the container is less than or equal to 20°C;

[0032] The sour wine accounts for 1 / 3 of the total mass of the sour wine;

[0033] The adding of the raw material and another portion of the sour wine specifically includes slowly adding the raw material and another portion of the sour wine;

[0034] The acidification temperature is 20 to 50°C;

[0035] The acidification time is greater than or equal to 50 min.

[0036] Preferably, in step 2), lowering the system temperature is specifically lowering the temperature to less than or equal to 35° C.;

[0037] The base includes sodium hydroxide;

[0038] The mass ratio of the alkali to chloroacetic acid is (2-2.2):1;

[0039] The alkali treatment time is greater than or equal to 1 hour.

[0040] Preferably, the temperature of the temperature-raising reaction is 70-80°C;

[0041] The temperature reaction time is 30 to 120 minutes;

[0042] The cooling for post-processing specifically includes cooling to less than or equal to 45°C for post-processing;

[0043] The post-treatment steps include neutralization and / or purification;

[0044] The post-treatment further includes drying and / or crushing steps.

[0045] The present invention also provides the use of the sodium carboxymethyl cellulose described in any one of the above technical solutions or the sodium carboxymethyl cellulose prepared by the preparation method described in any one of the above technical solutions in the field of papermaking.

[0046] The present invention provides a highly transparent ultra-low viscosity sodium carboxymethyl cellulose, wherein the degree of substitution of the sodium carboxymethyl cellulose is greater than or equal to 0.6; the 4% viscosity of the sodium carboxymethyl cellulose is less than or equal to 50 cps; the pH of the sodium carboxymethyl cellulose is 6.0-8.5; the transparency of the sodium carboxymethyl cellulose is less than or equal to 2.0; and the fiber content of the sodium carboxymethyl cellulose is less than or equal to 3.0. Compared with the prior art, the present invention aims at the problems existing in the existing ultra-low viscosity sodium carboxymethyl cellulose, especially the need for a higher requirement for the appearance of the product aqueous solution, requiring the transparency to be ≤2.0 and the fiber content to be ≤3.0, and requiring CMC to have better suspension ability and better solubility, etc. The present invention adopts natural cellulose (wood pulp, bamboo pulp, cotton, straw fiber, etc.) with low polymerization degree, improves product quality through process improvement, and obtains a high-transparency ultra-low-viscosity sodium carboxymethyl cellulose product with excellent characteristics. Its main quality indicators are as follows: degree of substitution ≥0.6, 4% B type ≤50mPa.s, pH value 6.0-8.5, transparency ≤2.0, and fiber content ≤3.0. It can meet customer requirements at the application end, especially the low-viscosity CMC required in special industrial fields. DETAILED DESCRIPTION

[0047] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than for limiting the claims of the invention. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The methods and applications of the present invention have been described by preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0048] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0049] The purity of all raw materials in the present invention is not particularly limited. The present invention preferably uses analytically pure raw materials or raw materials that meet the purity standards related to the preparation of paper-grade sodium carboxymethyl cellulose.

[0050] The abbreviations of all raw materials in the present invention are conventional abbreviations in the field and are clear and unambiguous in the field of their relevant uses. Those skilled in the art can uniquely identify them based on the abbreviations and corresponding uses, and they can be purchased from the market or prepared by conventional methods.

[0051] The present invention provides a high-transparency and ultra-low-viscosity sodium carboxymethyl cellulose, wherein the degree of substitution of the sodium carboxymethyl cellulose is greater than or equal to 0.6;

[0052] The 4% viscosity of the sodium carboxymethyl cellulose is less than or equal to 50 cps;

[0053] The pH of the sodium carboxymethyl cellulose is 6.0 to 8.5;

[0054] The transparency of the sodium carboxymethyl cellulose is less than or equal to 2.0;

[0055] The fiber content of the sodium carboxymethyl cellulose is less than or equal to 3.0.

[0056] In the present invention, the degree of substitution of the sodium carboxymethyl cellulose is greater than or equal to 0.6, more preferably 0.65 to 0.95, more preferably 0.7 to 0.9, and more preferably 0.75 to 0.85.

[0057] In the present invention, the 4% viscosity of the sodium carboxymethyl cellulose is less than or equal to 50 cps, more preferably 20 to 50 cps, more preferably 25 to 45 cps, and more preferably 30 to 40 cps.

[0058] In the present invention, the pH of the sodium carboxymethyl cellulose is 6.0 to 8.5, and may be 6.3 to 8.2, or 6.5 to 8.0.

[0059] In the present invention, the transparency of the sodium carboxymethyl cellulose is less than or equal to 2.0, more preferably 1.0 to 2.0, and more preferably 1.1 to 1.8.

[0060] In the present invention, the fiber content of the sodium carboxymethyl cellulose is less than or equal to 3.0, more preferably 2.0 to 3.0, and more preferably 2.2 to 2.8.

[0061] In the present invention, the sodium carboxymethyl cellulose is preferably prepared from natural cellulose.

[0062] In the present invention, the natural cellulose preferably includes one or more of wood pulp, bamboo pulp, cotton and straw fiber, and more preferably includes wood pulp, bamboo pulp, cotton or straw fiber.

[0063] In the present invention, the degree of polymerization of the natural cellulose is preferably 400-1000, more preferably 500-900, and even more preferably 600-800.

[0064] In the present invention, the 4% viscosity is preferably a 4% viscosity measured at 25° C. using a rotational viscometer.

[0065] In the present invention, the 4% viscosity is preferably 4% B-type viscosity.

[0066] In the present invention, the sodium carboxymethyl cellulose is preferably papermaking grade sodium carboxymethyl cellulose.

[0067] The present invention provides a method for preparing high-transparency and ultra-low-viscosity sodium carboxymethyl cellulose, comprising the following steps:

[0068] 1) crushing natural cellulose and then treating it with an oxidant to obtain a raw material;

[0069] Premix chloroacetic acid and alcohol into sour wine, put part of the sour wine into a container, then add the raw material and another part of the sour wine to acidify;

[0070] 2) After the acidification is completed, the system temperature is lowered, alkali is added for alkali treatment, the temperature is raised again for reaction, and the temperature is lowered for post-treatment to obtain sodium carboxymethyl cellulose.

[0071] The present invention firstly grinds natural cellulose and then treats it with an oxidant to obtain a raw material;

[0072] Premix chloroacetic acid and alcohol into sour wine, put part of the sour wine into a container, then add the raw material and another part of the sour wine for acidification.

[0073] In the present invention, the natural cellulose preferably includes one or more of wood pulp, bamboo pulp, cotton and straw fiber, and more preferably includes wood pulp, bamboo pulp, cotton or straw fiber.

[0074] In the present invention, the pulverization is preferably pulverized into a fluffy state.

[0075] In the present invention, the length of the pulverized natural cellulose is preferably less than or equal to 3 mm, more preferably less than or equal to 2.5 mm, and more preferably less than or equal to 2 mm.

[0076] In the present invention, the oxidant preferably includes one or more of an inorganic acid, an organic acid and ozone, and more preferably an inorganic acid, an organic acid or ozone.

[0077] In the present invention, the oxidant treatment time is preferably 0.5 to 1 h, more preferably 0.6 to 0.9 h, and more preferably 0.7 to 0.8 h.

[0078] In the present invention, the inorganic acid preferably includes hypochlorous acid.

[0079] In the present invention, the organic acid preferably includes oxalic acid.

[0080] In the present invention, the mass ratio of the chloroacetic acid to the alcohol is preferably 2.6:1.

[0081] In the present invention, the mixing temperature is preferably 50°C.

[0082] In the present invention, the temperature at which the portion of sour wine is placed in the container is preferably less than or equal to 20°C.

[0083] In the present invention, the partial sour wine preferably accounts for 1 / 3 of the total mass of the sour wine.

[0084] In the present invention, the adding of the raw material and another portion of the sour wine is preferably performed by slowly adding the raw material and another portion of the sour wine.

[0085] In the present invention, the acidification temperature is preferably 20 to 50°C, more preferably 25 to 45°C, and more preferably 30 to 40°C.

[0086] In the present invention, the acidification time is preferably greater than or equal to 50 min, more preferably greater than or equal to 60 min, and more preferably greater than or equal to 70 min.

[0087] After the final acidification is completed, the system temperature is lowered, alkali is added for alkali treatment, the temperature is raised for reaction, and the temperature is lowered for post-treatment to obtain sodium carboxymethyl cellulose.

[0088] In the present invention, in the step 2), the system temperature is preferably lowered to 35°C or less, more preferably 30°C or less, and more preferably 25°C or less.

[0089] In the present invention, the base preferably comprises sodium hydroxide.

[0090] In the present invention, the mass ratio of the alkali to chloroacetic acid is preferably (2-2.2):1, more preferably (2.04-2.16):1, and more preferably (2.08-2.12):1.

[0091] In the present invention, the alkali treatment time is preferably greater than or equal to 1 h, more preferably greater than or equal to 1.5 h, and more preferably greater than or equal to 2 h.

[0092] In the present invention, the temperature of the temperature-raising reaction is preferably 70 to 80°C, more preferably 72 to 78°C, and more preferably 74 to 76°C.

[0093] In the present invention, the temperature-raising reaction time is preferably 30 to 120 min, more preferably 50 to 100 min, and more preferably 70 to 80 min.

[0094] In the present invention, the cooling for post-treatment is preferably cooling to 45°C or less, more preferably 40°C or less, and more preferably 35°C or less.

[0095] In the present invention, the post-treatment step preferably includes neutralization and / or purification, more preferably neutralization or purification.

[0096] In the present invention, the post-treatment preferably further includes a drying and / or pulverizing step, more preferably a drying or pulverizing step.

[0097] The present invention is a complete and detailed overall technical solution, which can better improve the characteristics of high-transmittance ultra-low-viscosity sodium carboxymethyl cellulose products. The preparation method of the high-transmittance ultra-low-viscosity sodium carboxymethyl cellulose can specifically include the following steps:

[0098] A preparation method of a high-transparency and ultra-low-viscosity sodium carboxymethyl cellulose product:

[0099] ① In advance, crush natural cellulose (wood pulp, bamboo pulp, cotton, straw fiber, etc.) into fluff (no more than 3mm in length) and treat it with an oxidant (inorganic acid (such as hypochlorous acid), organic acid (such as oxalic acid), ozone, etc.) for 30 minutes to 1 hour. The concentration of inorganic acid and organic acid needs to be adjusted according to the final requirements of the product;

[0100] ②Preheat the water bath to 50℃ in advance, mix chloroacetic acid and alcohol into acid wine in advance (the mass ratio of chloroacetic acid to alcohol is 2.6), cool the acid wine to below 20℃ in advance, add 1 / 3 of the acid wine to the three-necked flask, start stirring, and then slowly add natural cellulose and the remaining acid wine. The temperature of the acidification process is controlled at 20-50℃, and the acidification time is: more than 50min;

[0101] ③ Adjust the water bath temperature to below 35°C, add liquid alkali (sodium hydroxide solution, concentration of 50% or more) 2-2.2 times the acid mass and treat for more than 1 hour, continue stirring after adding to carry out alkali treatment;

[0102] ④ Raise the temperature to 70-80°C and carry out constant temperature reaction for 30-120 minutes, then cool down to below 45°C for neutralization and purification;

[0103] ⑤Finally, the prepared CMC is dried and crushed to obtain a high-transparency and ultra-low-viscosity sodium carboxymethyl cellulose product.

[0104] The high-transparency and ultra-low-viscosity sodium carboxymethyl cellulose product prepared by the present invention has the following indicators:

[0105] Degree of substitution: ≥0.6;

[0106] 4% viscosity (Brookfield LVT, 25℃): ≤50cps;

[0107] pH: 6.0-8.5;

[0108] Transparency ≤ 2.0;

[0109] Fiber content ≤3.0.

[0110] The present invention provides the use of the sodium carboxymethyl cellulose described in any one of the above technical solutions or the sodium carboxymethyl cellulose prepared by the preparation method described in any one of the above technical solutions in the field of papermaking.

[0111] The above content of the present invention provides a high-transmittance ultra-low viscosity sodium carboxymethyl cellulose product and its preparation method and application. The present invention adopts natural cellulose (wood pulp, bamboo pulp, cotton, straw fiber, etc.) with a low degree of polymerization, improves the product quality through process improvement, and obtains a high-transmittance ultra-low viscosity sodium carboxymethyl cellulose product with excellent characteristics. Its main quality indicators have reached the degree of substitution ≥ 0.6, 4% B type ≤ 50mPa.s, pH value 6.0-8.5, transparency ≤ 2.0, fiber content ≤ 3.0, which can meet customer requirements at the application end, especially the low-viscosity CMC required in special industrial fields.

[0112] In order to further illustrate the present invention, a high-transmittance and ultra-low-viscosity sodium carboxymethyl cellulose product provided by the present invention and its preparation method and application are described in detail in combination with the following examples. However, it should be understood that these examples are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the characteristics and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following examples.

[0113] Example 1

[0114] ① In advance, crush natural cellulose (wood pulp, bamboo pulp, cotton, straw fiber, etc.) into fluff (no more than 3mm in length) and treat it with an oxidant (inorganic acid (such as hypochlorous acid), organic acid (such as oxalic acid), ozone, etc.) for 30 minutes to 1 hour. The concentration of inorganic acid and organic acid needs to be adjusted according to the final requirements of the product;

[0115] ②Preheat the water bath to 50℃ in advance, mix chloroacetic acid and alcohol into acid wine in advance (the mass ratio of chloroacetic acid to alcohol is 2.6), cool the acid wine to below 20℃ in advance, add 1 / 3 of the acid wine to the three-necked flask, start stirring, and then slowly add natural cellulose and the remaining acid wine. The temperature of the acidification process is controlled at 20-50℃, and the acidification time is: more than 50min;

[0116] ③ Adjust the water bath temperature to below 35°C, add liquid alkali (sodium hydroxide solution, concentration of 50% or more) 2-2.2 times the acid mass and treat for more than 1 hour, continue stirring after adding to carry out alkali treatment;

[0117] ④ Raise the temperature to 70-80°C and carry out constant temperature reaction for 30-120 minutes, then cool down to below 45°C for neutralization and purification;

[0118] ⑤Finally, the prepared CMC is dried and crushed to obtain a high-transparency and ultra-low-viscosity sodium carboxymethyl cellulose product.

[0119] Through the above preparation method, by adjusting the adding method, adding amount, reaction temperature and reaction time of the viscosity reducer, the ultra-low viscosity CMC transparency fiber produced in the embodiment of the present invention is significantly improved compared with the previous one.

[0120] See Table 1, which is a comparison of the indices of the high-transparency ultra-low-viscosity sodium carboxymethyl cellulose product prepared in the embodiment of the present invention and the commercially available papermaking grade ultra-low-viscosity sodium carboxymethyl cellulose product.

[0121] Table 1

[0122] Indicator name Degree of substitution 4% viscosity (Brookfield LVT, 25℃) transparency fiber Paper Grade 0.85 40cps 2.0 4 Improvement ① 0.85 40cps 1.5 2.9 Improvement ② 0.85 40cps 1.5 2.9

[0123] Transparency and fiber indexes are standard sample comparison indexes. The smaller the number, the better the transparency or fiber. It can be seen that after the process adjustment, the transparency and fiber of CMC have been significantly improved.

[0124] Ultra-low viscosity CMC mesh performance verification

[0125] Experimental steps:

[0126] ① Weigh 75g of CMC sample and transfer it into a 500mL ground-mouth bottle with a stopper. Measure 425g of water (prepared into a 15% CMC solution) into the wide-mouth bottle. Place the wide-mouth bottle under the stirrer, turn on the stirrer power, adjust the speed to 200-400 rpm, and slowly add the CMC sample. After the sample is completely added, slowly adjust the stirring speed to 900±100 rpm and stir for 2-3h until the sample is completely dissolved and evenly dissolved.

[0127] ②Put the wide-mouth bottle containing the prepared sample solution into a constant temperature water bath at 25±0.2℃ for 1h. Check the temperature of the CMC solution. If the value is within the range of 25±0.2℃, test the viscosity.

[0128] ③Control the solution viscosity (Brookfield LVT, 25℃) in the range of 3000-4000, fix a 200-mesh sieve on the top of a 500ml measuring cylinder, pour the prepared solution on the sieve, and record the natural permeability in 5 minutes.

[0129] See Table 2, which is a comparison of the mesh penetration performance of the high-transmittance ultra-low-viscosity sodium carboxymethyl cellulose product prepared in the embodiment of the present invention and the commercially available papermaking grade ultra-low-viscosity sodium carboxymethyl cellulose product.

[0130] Table 2

[0131] Indicator name Degree of substitution 15% viscosity (Brookfield LVT, 25℃) fiber Net penetration (ml) Paper Grade 0.85 3580cps 4 150 Improvement ① 0.85 3620cps 2.9 280 Improvement ② 0.85 3550cps 2.9 260

[0132] From the experimental comparison results, it can be seen that the CMC produced after the process improvement has less fiber than the original CMC aqueous solution, and the mesh penetration is significantly improved, and the flow pattern is better and continuous during the mesh penetration process.

[0133] Ultra-low viscosity CMC stability verification

[0134] Through process optimization, the quality of CMC is improved on the basis of ultra-low viscosity CMC for papermaking grade. This optimization needs to be demonstrated through relevant application experiments.

[0135] Main reagents: conductive materials, hydrofluoric acid, concentrated nitric acid, CMC, distilled water.

[0136] Experimental steps:

[0137] ①Prepare 5L of distilled water in a large beaker, add 50g of CMC and stir thoroughly until it is completely dissolved, and record the time when CMC is completely dissolved;

[0138] ②Add 50g hydrofluoric acid and 50g concentrated sulfuric acid into the CMC solution in sequence and stir for 30 minutes;

[0139] ③Put the prepared conductive material into the stirred solution;

[0140] ④Stability corrosion for 5 days, and observe the amount of attachment on the conductive material after 5 days.

[0141] See Table 3 and Table 4, which are comparisons of the solubility and attachment of the high-transparency ultra-low viscosity sodium carboxymethyl cellulose product prepared in the embodiment of the present invention and the commercially available paper-making grade ultra-low viscosity sodium carboxymethyl cellulose product in different pH experimental systems.

[0142] Table 3

[0143]

[0144] Table 4

[0145]

[0146] The application test environments with two different pH values ​​are mainly used to measure the acid resistance of the developed CMC.

[0147] The adhesion amount is divided into 5 levels from more to less, namely more, more, medium, less, and less.

[0148] Through data comparison, it can be seen that the solubility of CMC has been improved after the process improvement, and the attachment of conductive materials has been reduced, indicating that the quality of CMC has been improved, and the acid resistance has also been improved.

[0149] The above is a detailed introduction to a high-transmittance ultra-low viscosity sodium carboxymethyl cellulose product provided by the present invention, its preparation method and application. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention, including the manufacture and use of any device or system, and the implementation of any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. Application of high-transparency and ultra-low-viscosity sodium carboxymethyl cellulose in the field of papermaking; The degree of substitution of the sodium carboxymethyl cellulose is greater than or equal to 0.6; The 4% viscosity of the sodium carboxymethyl cellulose is less than or equal to 50 cps; the 4% viscosity is the 4% B-type viscosity measured by a rotational viscometer at 25° C.; The pH of the sodium carboxymethyl cellulose is 6.0-8.5; The transparency of the sodium carboxymethyl cellulose is less than or equal to 2.0; The fiber content of the sodium carboxymethyl cellulose is less than or equal to 3.0; The preparation method of the high-transparency and ultra-low-viscosity sodium carboxymethyl cellulose comprises the following steps: 1) The natural cellulose is crushed and then treated with an oxidant to obtain a raw material; Premix chloroacetic acid and alcohol into sour wine, put part of the sour wine into a container, then add the raw material and another part of the sour wine to acidify; 2) After the acidification is completed, the system temperature is lowered, alkali is added for alkali treatment, the temperature is raised again for reaction, and then the temperature is lowered for post-treatment to obtain sodium carboxymethyl cellulose.

2. The use according to claim 1, characterized in that: The sodium carboxymethyl cellulose is prepared from natural cellulose; The natural cellulose includes one or more of wood pulp, bamboo pulp, cotton and straw fiber.

3. The use according to claim 2, characterized in that: The degree of polymerization of the natural cellulose is 400-1000; The sodium carboxymethyl cellulose is papermaking grade sodium carboxymethyl cellulose.

4. The use according to claim 1, characterized in that: The natural cellulose includes one or more of wood pulp, bamboo pulp, cotton and straw fiber; The crushing is specifically crushing into a fluffy state; The length of the crushed natural cellulose is less than or equal to 3 mm.

5. The use according to claim 1, characterized in that: The oxidant includes one or more of an inorganic acid, an organic acid and ozone; The inorganic acid includes hypochlorous acid; The organic acid includes oxalic acid; The oxidant treatment time is 0.5 to 1 h.

6. The use according to claim 1, characterized in that: The mass ratio of the chloroacetic acid to the alcohol is 2.6:1; The premix temperature was 50°C.

7. The use according to claim 1, characterized in that: The temperature of the part of sour wine placed in the container is less than or equal to 20°C; The sour wine accounts for 1 / 3 of the total mass of the sour wine; The adding of the raw material and another portion of the sour wine specifically includes slowly adding the raw material and another portion of the sour wine; The acidification temperature is 20-50°C; The acidification time is greater than or equal to 50 minutes.

8. The use according to claim 1, characterized in that: In the step 2), lowering the system temperature specifically involves lowering the temperature to less than or equal to 35°C; The base includes sodium hydroxide; The mass ratio of the alkali to chloroacetic acid is (2-2.2):1; The alkali treatment time is greater than or equal to 1 hour.

9. The use according to claim 1, characterized in that: The temperature of the temperature-raising reaction is 70-80°C; The temperature-raising reaction time is 30 to 120 minutes.

10. The use according to claim 1, characterized in that: The cooling for post-processing specifically includes cooling to less than or equal to 45°C for post-processing; The post-treatment steps include neutralization and / or purification; The post-treatment further includes drying and / or crushing steps.

Citation Information

Patent Citations

  • Preparation method of low-viscosity sodium carboxymethyl cellulose

    CN114773489A